Comparative study on Bartonella infection in spleen and kidney of small mammals from Mile City and Lianghe County, Yunnan Province - Fu, Rong; Yin, Jia-Xiang; He, Ping; Chen, Yan; Luo, Yi; Liu, Ping-Guo; Guo, Shuang-Ling (Frontiers in Veterinary Science, 2025)
BackgroundBartonellosis is a zoonotic infectious disease caused by Bartonella spp. Small mammals are the most important hosts of Bartonella and play an important role in its long-term maintenance and spread. The multi-organ studies help understand the Bartonella prevalence of hosts more systematically and comprehensively. This study aimed to investigate the prevalence of Bartonella in small mammals and explore the genetic diversity of the infected strains and the influencing factors from Mile City and Lianghe County, Yunnan Province.MethodsSmall mammals were captured in Mile City and Lianghe County of Yunnan Province from July to August 2019. Spleen and kidney tissues were collected and the gltA gene was amplified to detect and analyze the prevalence of Bartonella in two regions and two organs.ResultsThe prevalence of Bartonella in small mammals was 14.29% (43/301). Lianghe County’s risk of infection was 3.79-fold (95%CI: 1.39–13.35) compared to that of Mile City. The risk of infection in Rattus tanezumi was increased by 90% compared to Suncus murinus (95%CI: 0.01–0.63). The small mammals with tail lengths > 132 mm infected by Bartonella were 6.34 folds than that with tail lengths ≤ 132 mm (95%CI: 1.87–23.39). The spleen had a higher infection rate of 12.11% (35/289) than the kidney at 7.33% (22/300) (χ2 = 4.966, p = 0.026). There were no statistically significant differences in the prevalence of Bartonella among small mammals with different habitats, sex, age, flea infestation status, body weight, body length, hindfoot length, and ear height. Five Bartonella species were isolated in seven species of small mammals. Bartonella tribocorum is the dominant species in both regions, and it has a genetic relationship with the zoonotic pathogen Bartonella elizabethae.ConclusionThis study showed the prevalence of Bartonella in small mammals from Mile City and Lianghe County of Yunnan Province was high, and there were more types of Bartonella infection species. The spleen was more conducive to the growth and reproduction of Bartonella. The results of the study will help to prevent and control Bartonella infection and transmission to humans from small mammals in the two regions and provide a reference basis for further research on Bartonella infection in Yunnan or other similar regions.